Improved Soil Behavior: A Case Study of Reconstituted Soil from Khasibazar, Kathmandu - Dahal, Bhim Kumar; Baidya, Purnima; Dahal, Diwash; KC, Diwakar (Journal of Engineering Issues and Solutions, 2025)
The study explores the behavior of high-plastic organic soil modified with varying cement contents (5%, 10%, and 15%) subjected to comprehensive laboratory testing. Analyses encompass physical, chemical, microstructural, and mechanical behavior assessments. The result implies that reconstitution significantly impacts physical attributes. Specific gravity initially decreases but reverts to its initial value at 15% cement content. Liquid and plastic limits increase with increasing cement content, while the plasticity index decreases initially and increases after a certain cement content. Similarly, soil minerals primarily comprising quartz, kaolinite, and biotite affect soil particle cementation and aggregation, leading to larger particle sizes, which was verified by SEM imaging, which revealed a more flocculated microstructure and larger particle sizes in cement- treated soil. Furthermore, two power functions are developed first to relate the soil strength with cement content, ranging from 89.83-601.76 kPa at 5% and 15% cement content, respectively, and second to relate failure strain with cement content, which demonstrates the enhanced brittleness characteristics of cement-treated soil. Similarly, an exponential function of cement content well represented the primary yielding strength (p’yi ; 10-325 kPa) when cement increased in similar percentages as above. Additionally, the UCS and p’yi , are strongly correlated, following a power function. Finally, this comprehensive analysis underscores the pivotal role of cement content in soil reconstitution. It emphasizes the significant changes in its physical, chemical, microstructural, and mechanical properties, offering insights vital for mitigating challenges in infrastructure development involving lacustrine deposits.